DINAMIKA PEMEKARAN KAMPUNG DAN BENTENG TERBUKA PAPUA - Suryawan, I Ngurah (KRITIS, 2016)
Proliferation of villages in Papua is a strategy of village leaders and the community in order to access development. This paper is intended to describe the dynamics of proliferation of the villages in Papua and its impacts. One aspects highlighted in this paper is the fact that due to the proliferation of villages, the community in Papua gains more access to globalisation. Consequently, their interaction to the global world stimulates ideas and dreams for social transformation.